2013
DOI: 10.3389/fpls.2013.00313
|View full text |Cite
|
Sign up to set email alerts
|

Barley responses to combined waterlogging and salinity stress: separating effects of oxygen deprivation and elemental toxicity

Abstract: Salinity and waterlogging are two major factors affecting crop production around the world and often occur together (e.g., salt brought to the surface by rising water tables). While the physiological and molecular mechanisms of plant responses to each of these environmental constraints are studied in detail, the mechanisms underlying plant tolerance to their combined stress are much less understood. In this study, whole-plant physiological responses to individual/combined salinity and waterlogging stresses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 38 publications
11
59
0
1
Order By: Relevance
“…A possible explanation could be that these QTL affect other genes responsible for changes in the metabolic processes causing toxicity (Zeng et al 2013), ethylene production initiating aerenchyma formation or some of the other processes not directly related to energy production (Agarwal and Grover 2006;Colmer and Voesenek 2009;Ahmed et al 2013). However, the meta-analysis did confirm the presence of QTLs on 4H and 7H.…”
Section: Discussionmentioning
confidence: 45%
“…A possible explanation could be that these QTL affect other genes responsible for changes in the metabolic processes causing toxicity (Zeng et al 2013), ethylene production initiating aerenchyma formation or some of the other processes not directly related to energy production (Agarwal and Grover 2006;Colmer and Voesenek 2009;Ahmed et al 2013). However, the meta-analysis did confirm the presence of QTLs on 4H and 7H.…”
Section: Discussionmentioning
confidence: 45%
“…The decline in root extension is a consequence of a decrease in the uptake and balance of nutrients. Zeng et al (2015) showed that, compared to salinity stress, the combined stress of aeration and salinity doubles the Na + concentration and decreases K + c in barley leaves by 40%. These effects are influenced by soil redox potential and accumulation of Mn and Fe under waterlogged conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Individual leaves were placed in (5 x 8 cm) brown paper bags and oven-dried at 70 o C for 48 h. The dry weight (DW) was then recorded and LWC was calculated on a fresh weight basis using the following equation (Kirkman, 2005;Zeng et al, 2013):…”
Section: Leaf Water Contentmentioning
confidence: 99%
“…During water stress at the seedling stage, the percentage leaf water content (LWC) of the third leaf was calculated (Kirkman, 2005;Zeng et al, 2013). blade was excised for quantification of percentage LWC; and (e) proline was quantified following the protocol described by Bates et al (1973).…”
Section: Measurementsmentioning
confidence: 99%